โปรแกรมเปิดภาพทางการแพทย์ด้วยหลักเกณฑ์มาตรฐานไดคอม และการประมวลผลภาพทางการแพทย์: DICOM Medical Imaging Viewer and Medical Image Processing - Suapang, Piyamas (Asian Health, Science and Technology Reports, 2010)
The purpose of this research is to study on the design and construction of DICOM Medical Imaging Viewer and Medical Image Processing by MATLAB 7.2. based on the principle of medical imaging, medical image processing and computer in medicine. The constructed DICOM Medical Imaging Viewer and Medical Image Processing can be operated in 3 functions, i.e. 1) open single frame 2) open multiframes, each of which can exhibit information in .dcm file format and 3) digital image processing. These included histogram, crop image, black and white adjustment, contrast enhancement and edge detection. The functions employed were developed as built-in submenus. The results of functional testing of the constructed DICOM Medical Imaging Viewer and Medical Image Processing showed that the program can open and display medical image and it’s information with no distortion when compared withs the original image and every function worked could for medical image processing. It was also found that although each function was suitable for a different purpose, simmultaneous use of all functions together might be necessary to improve the quality of images.